Automatic Task Provisioning and Routing Framework for Carrier Robots in Smart Factory with Edge Computing - Philip Tobianto Daely; Oktavia Ayu Permata; Bernadus Anggo Seno Aji (International Journal of Recent Technology and Applied Science (IJORTAS), 2025)
This paper proposed a pickup and delivery (P&D) task provisioning and vehicle routing framework for carrier robots in a factory with edge servers assisting as the intermediary between robots and working stations, where the task requests come. The carrier robots must pick up and deliver each assigned load from and to designated locations with minimal traveled distance and without violating designated constraints. Edge servers are utilized to facilitate communication between the main server and delivery robots and assist the main server in deciding the best robot for each incoming task request and the updated route to facilitate execution of tasks by each carrier robot. The problem of pickup and delivery for each robot is modeled based on Dial-a-Ride Problem, and a discrete bio-inspired algorithm is proposed to solve this problem. The tasks are distributed to edge servers and carrier robots by taking their service loads into account. The simulation results show that the proposed framework can provide an effective solution towards optimizing the pickup and delivery process in a smart factory.